Shopping centre growth and the decline of the central business district in an urban system: A case study of the Ottawa-Hull Census Metropolitan Area. - Lendvay-Zwickl, Joseph B. (University of Ottawa (Canada), 1977)
Abstract not available.
Keywords: Geography.